Ultra-fast shock-wave combustion synthesis of nanostructured silicon from sand with excellent Li storage performance. Issue 6 (15th March 2019) - Kamali, Ali Reza; Haghighat-Shishavan, Safa; Nazarian-Samani, Masoud; Rezaei, Asma; Kim, Kwang-Bum
Abstract : A novel shock-wave combustion synthesis method was developed for ultra-scalable, clean and energy efficient conversion of sand to nanostructured silicon with excellent performance as an anode material for Li-ion batteries. Abstract : The available technologies used for the preparation of elemental silicon (Si), including the traditional carbothermal technology of producing bulk Si, pyrolysis-based methods of producing Si nanoparticles and the metallothermic fabrication of state-of-the-art nanostructured Si powder are all considered energy- and time-intensive processes, with associated environmental issues. Herein, for the first time, a combustion synthesis methodology, involving the occurrence of an ignition event followed by the immediate completion of the process, is used for the preparation of nanostructured Si for energy applications. In this process, Si powders are directly extracted from sea sand by a novel ultra-fast shock-wave combustion synthesis (SWCS), in which KClO4 is employed as the combustion agent to promote the immediate reduction of SiO2 . The reaction is completed at an ignition temperature of about 550 °C, requiring virtually no dwell time. The process is scalable, green and carbon-free with a low energy consumption of about 100 kW h per ton, less than one percent of that of the current technologies. The Si product possesses a nanostructured mesoporous integrated sheet-like (NMIS) morphology, with an excellent and stable Li storage performance. The mechanism involved in the proposed method is also discussed. The feasibility of the SWCS approach for the preparation of Si is demonstrated in this article, based on which a variety of nanostructured materials is expected to be produced by this method.